(1.)  x + 7 = 13                here is the problem

-7  -7          subtract 7 from each side
____________
x =  6           subtract

result:  x = 6

(2.)    8 + n = 5              here is the problem

-8      -8        subtract 8 from each side
_______________
n = -3       subtract

result:    n = -3

(3.)   y - 4 = 13             here is the problem

+4    +4         add 4 to each side
______________

result:  y = 17

(4.)  3 + y = 17               here is the problem

-3     -3          subtract 3 from each side
_______________
y = 14        subtract

result:  y = 14

(5.) -8 + z = 30              here is the problem

+ 8    + 8              add 8 to each side
_____________

result:    z = 38

(6.)   -12 + z = 1                here is the problem

+  12      +12              add 12 to each side
_______________

result:   z = 13

(7.)   m + 3 = 1              here is the problem

-3  -3          subtract 3 from each side
________________
m    =  -2          subtract

result:  m = -2

(8.)   r + 9 = -19             here is the problem

-9    -9      subtract 9 from each side
_________________
r     = -28          subtract

result:  r = -28

(9.)   -8 + t = -13             here is the problem

+    8        +8           add 8 to each side
_________________